Landscape between ideology and the aesthetic : Marxist essays on British art and art theory, 1750-1850 - Hemingway, Andrew (Historical materialism book series, 2017)
At a time of growing interest in relations between Marxism and Romanticism, Andrew Hemingway's essays on British art and art theory reopen the question of Romantic painting's ideological functions and, in some cases, its critical purchase. Half the volume exposes the voices of competing class interests in aesthetics and art theory in the tumultuous years of British history between the American Revolution and the 1832 Parliamentary Reform Act. Half offers new perspectives on works by some of the most important landscape painters of the time: John Constable, J.M.W. Turner, John Crome, and John Sell Cotman. Four essays are hitherto unpublished, and the remainder have been updated and in several cases substantially rewritten for this volume.